2022
DOI: 10.1146/annurev-clinpsy-072220-021819
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in African American Adolescents: Understanding Risk by Studying Resilience

Abstract: Historically, suicide rates for African American adolescents have been low,relative to rates for youth of other racial-ethnic backgrounds. Since 2001, however, suicide rates among African American adolescents have escalated: Suicide is now the third leading cause of death for African American adolescents. This disturbing trend warrants focused research on suicide etiology and manifestation in African American adolescents, along with culturally sensitive and effective prevention efforts. First, we revisit leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 96 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Factors protecting against suicide in young people remain poorly understood. Family cohesion, increased access to care, faith/spiritual factors, cognitive flexibility and emotion regulation skills, and strong interpersonal relationships have been identified as conferring protection against suicidal behavior in young people 1136373839. Although negative aspects of the internet/social media have generated concern, potential positive aspects such as connection, reduced isolation, and community may prove to be protective 40.…”
Section: Epidemiologymentioning
confidence: 99%
“…Factors protecting against suicide in young people remain poorly understood. Family cohesion, increased access to care, faith/spiritual factors, cognitive flexibility and emotion regulation skills, and strong interpersonal relationships have been identified as conferring protection against suicidal behavior in young people 1136373839. Although negative aspects of the internet/social media have generated concern, potential positive aspects such as connection, reduced isolation, and community may prove to be protective 40.…”
Section: Epidemiologymentioning
confidence: 99%
“…Researchers measuring suicidal ideation, depressive symptoms, social support, and resilience need to consider socioecological and cultural differences that are unique to Chinese adolescents compared to those of other racial and ethnic backgrounds. 33 This sample of undergraduates is not nationally representative. The data was made available through the Mental Health Center assessing the mental health of undergraduates during the COVID-19 epidemic at a university.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Resilience is the process of effectively coping with uncertainty during the COVID-19 pandemic, and the enhancement of resilience may reduce the risk of suicide. 48 There are gender differences in suicide and resilience among adolescents, 33 as girls are twice as likely as boys to be diagnosed with depressive symptoms that may be life-threatening. 19 This study found that male undergraduates had a higher risk of suicidal ideation, though another study found that female adolescents had a higher risk of suicidal ideation among 5,175 Chinese adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to systemic and structural racism, African American adolescents contend with an array of unique contextual risk‐factors for suicidal ideation over time (e.g., racial discrimination, community violence; Farrell et al, 2019; Madubata et al, 2022). Consequently, longitudinal patterns and predictors of ideation in these adolescents may differ from adolescents from other racial/ethnic backgrounds (Kim et al, 2019; Robinson et al, 2022). Further, because most African American adolescents will experience discrimination (Smith‐Bynum et al, 2014), and those living in urban, low‐resourced areas also frequently experience distinct contextual risk‐factors for ideation such as exposure to community violence (Copeland‐Linder et al, 2011; Richards et al, 2015), a relatively large proportion of African American youth may report suicidal ideation at some point during adolescence.…”
mentioning
confidence: 99%